(untitled) (International Journal of Innovative Technologies in Economy, 2022)
In this article, we analyze the measures against pollution in river basins that follow the European Water Framework Directive (European Commission, 2000) and propose a methodology for assessing their economic effectiveness. Compared to other similar studies (Berbel et al., 2018), the presented methodology has been developed and tested in rivers where water pollution is a result of mining activities. In terms of economic theory, the methodology can be summarized as follows: The cost-effectiveness analysis used to select the optimal mix of costs is integrated into the cost-benefit analysis to assess the cost-effectiveness of the proposed measures. The methodology has been tested on a case study of the East Aegean Region and recommendations for the region have been made for the next five-year period of the Directive.